CEO tournament incentives and corporate debt contracting - Ghosh, Chinmoy; Huang, Di; Nguyen, Nam H.; Phan, Hieu V. (Journal of Corporate Finance, 2023)
This study examines the relation between CEO tournament incentives, proxied by the difference between CEO pay and the median pay of the senior executives of a given firm, and corporate debt contracting. We find negative relations between CEO pay gap and the cost of debt and default risk, and a positive relation between CEO pay gap and debt maturity. Further analysis indicates that the results are stronger for firms with near-retirement CEOs, which are more likely to run CEO tournaments. Our evidence suggests that creditors view tournament incentives favorably and are willing to provide better debt terms.